Therapeutic ultrasound: an innovative approach for targeting neurological disorders affecting the basal ganglia - Singh, Anurag; Reynolds, John N. J. (Frontiers in Neuroanatomy, 2024)
The basal ganglia are involved in motor control and action selection, and their impairment is manifest in movement disorders including Parkinson's disease, dystonia, and others. The complex neuronal circuitry of the basal ganglia is seated deep inside the brain and presents significant treatment challenges. Conventional treatment strategies, such as invasive surgeries and medications, may have 7me-limited effectiveness and result in considerable side effects. Noninvasive ultrasound treatment approaches are becoming increasingly recognised for their therapeutic potential for reversibly permeabilising the blood-brain barrier, targeted therapeutic delivery deep into the brain, and neuromodulation. Studies on animals and early clinical trials using ultrasound as a therapeutic modality have begun to demonstrate promising outcomes for controlling symptom severity while preserving neural tissue, and could improve quality of life for patients living with basal ganglia impairments. This review article explores the therapeutic frontiers of ultrasound technology, describing the brain mechanisms that are triggered and engaged through ultrasound. We highlight how this cutting-edge method could transform the way neurological disorders associated with the basal ganglia are managed, opening the door to less invasive and more effective treatments.